Video Works 1970-1999 - Wegman, William ([Houston] : Artpix, 2006)
Disc One Spit Sandwich (1970) (15 min.)## Selected Works: Reel 1 (1970) (30 min.)## Selected Works: Reel 2 (1972) (20 min.)## Selected Works: Reel 3 (1973) (22 min.)## Selected Works: Reel 4 (1973-1974) (21 min.)## Selected Works: Reel 5 (1974-1975) (31 min.). ##Disc Two Selected Works: Reel 6 (1975-1976) (20 min.)## Gray hairs (1976) (5 min.)## Selected Works: Reel 7 (1977) (18 min.)## Reel 8 (1997-1998) (26 min.)## Reel 9 (1999) (20 min.).
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Wegman, William